Strategi Fundrising Zakat: Literasi Zakat Produktif dan Zakat Profesi (Studi pada Bmt Muda Jatim Mitra Inisiatif Zakat Indonesia) - Indah Rofiqoh, Siti Nur; Alauddin, Mohammad; Hasanah, Niswatun (Proceedings of Annual Conference on Community Engagement, 2018)
: Productive zakat is a new scheme for the distribution of zakat funds in partnership BMT MUDA-IZI. How is the fundrising strategy through literacy of the distribution of productive zakat funds and the determination of professional zakat alms? are the research problems. Through a descrptive qualitative analysis approach, the result of this research conclude that the scheme for disributing productive zakat funds is optimized to reach the long term targets, give productive zakat education to the community and choose potential sector. The farm sector and cast concrete product of Yayasan Darul Ihlas Sidayu Gresik business units are the selected sectors. Literacy of professional zakat in partnership BMT MUDA-IZI is based on agricultural-zakat and paid according to the period of agreement.